2007
DOI: 10.2332/allergolint.r-06-135
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and Related Compounds as Anti-Allergic Substances

Abstract: The prevalence of allergic diseases has increased all over the world during the last two decades. Dietary change is considered to be one of the environmental factors that cause this increase and worsen allergic symptoms. If this is the case, an appropriate intake of foods or beverages with anti-allergic activities is expected to prevent the onset of allergic diseases and ameliorate allergic symptoms. Flavonoids, ubiquitously present in vegetables, fruits or teas possess anti-allergic activities. Flavonoids inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
213
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(215 citation statements)
references
References 74 publications
2
213
0
Order By: Relevance
“…In addition, it is necessary to have a series of evidence to support both in vitro and in vivo effectiveness of these promising materials. Several flavonoids including quercetin, luteolin, kaempferol and myricetin are known to inhibit histamine release from human basophils and rat basophilic leukemia cells [12,14]. It has been also reported that some flavonoid glucosides or glucuronides exhibit the inhibitory effect on IgE-mediated degranulation [1,2,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is necessary to have a series of evidence to support both in vitro and in vivo effectiveness of these promising materials. Several flavonoids including quercetin, luteolin, kaempferol and myricetin are known to inhibit histamine release from human basophils and rat basophilic leukemia cells [12,14]. It has been also reported that some flavonoid glucosides or glucuronides exhibit the inhibitory effect on IgE-mediated degranulation [1,2,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant effect of spinach is reported to be mainly due to the flavonoid compounds such as spinacetin glucoside, patuletin glucoside and dioxol flavonoid [5,7,10]. On the other hand, some flavonoid compounds isolated from other plants, including quercetin, kaempherol and so on have been shown to inhibit histamine release from rat basophilic leukemia cells [2,[12][13][14][15][16][17][18]. However, it is unknown that spinach has an inhibitory component on both IgE-mediated degranulation from the cells and in vivo allergic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alteration in secretion of these colony stimulating factors impair proliferation and differentiation of leukocytes. Because studies have shown that flavonoids inhibit IL-1β-stimulated granulocyte-colony stimulating factor expression and subsequent neutrophil differentiation as well as suppressing the expression of granulocyte/monocytecolony stimulating factor [23,24] could suggest that Tetrapleura tetraptera pod extract inhibited proliferation and differentiation processes required to necessitate neutrophil production resulting in the reduction in the peripheral neutrophil count. Besides inhibition of granulocyte-colony stimulating factor and granulocyte/monocyte-colony stimulating factor, apigenin and chalcones have been shown to inhibit interleukins-6and blocked tumor necrosis factor-α [25,26].…”
Section: Mid Cellsmentioning
confidence: 99%
“…They exert several biological benefits for humans, such as antioxidant, anti-inflammatory, antibacterial, anti-viral, anti-angionic, anti-allergic and immune-modulating effects. An appropriate intake of flavonoids may therefore be expected to prevent chronic diseases including allergic diseases 7,[14][15][16] . Third, the inhibitory effect of flavonoids on activation of high-affinity IgE receptor (FcRI)-expressing cells, such as mast cells and basophils is well known, and was found to also inhibit histamine release and synthesis of leukotriene or other chemical mediators 7,19 .…”
Section: Flavonoids May Constitute Complementary Medicine For Allergimentioning
confidence: 99%